Transporte de ozônio em hidrogerador de 311 mva: modelagem fluidodinâmica tridimensional de máquina elétrica dos elementos finitos. através do método - GIROTTO, Gustavo Gaspar (Universidade Federal do Pará, 2025)
In this work, a three-dimensional numerical model of fluid dynamics is developed for a single 311 MVA power generator unit in a hydroelectric power plant using the finite element method. The goal is to study the ozone transport mechanisms within the enclosed structure of the electrical generator machine. Ozone is produced by partial discharges related to some faults in the stationary bars. To analyze the ozone transport from localized sources, a three-dimensional fluid dynamics model of an operational hydrogenerator is developed and presented for the first time. The model has a high level of geometric details. Additionally, a new proposal to simplify the modeling of radiators is implemented and validated. The modeled structure is based on an electrical machine from the Campos Novos hydrogenerator and consists of 378 coil-type stationary bars made of mica-coated copper and, externally, by a layer of semiconductor coating. Other parts are also represented, including the stationary core and air deflectors made of stainless steel, copper radiators, the rotor with its epoxy surface, and the floor and external walls made of concrete. In the fluid dynamics model, a finite element mesh is designed to represent the air regions inside the hydrogenerator and the surfaces of materials reacting with ozone (with their respective reaction rates), where air flow and ozone transport are modeled using the Navier-Stokes equations and the law of mass conservation. Partial discharge sources are represented by ozone sources with prismatic shapes, positioned on the surfaces of stationary bars. Ozone concentrations are calculated inside and around the generator machine. The rotor radius is 3.8075 m, and its rotation frequency is 200 RPM. The radial air velocity due to interpolar ventilation is also considered (2.2 m/s, as experimentally verified on-site). The radial velocity near the radiators is 3 m/s. It is concluded that the ozone transport profile is influenced by the source position on the stationary bars, so determining the source location is possible and depends on determining the local and global maximum ozone concentration areas on the radiators.